Ideas and practices of the New Public Management - Czarnecki, Krzysztof (Journal of Public Governance, 2012)
By reviewing the relevant literature, the article aims at characterizing ideas, doctrines, instruments and values of the New Public Management – one of the dominant modern public management narratives. In the first part, against the background of changes of public sector policies in 1980s and 1990s, the origins of NPM have been presented. Then its intelectual roots, based on the New Institutional Economics, neoliberalism and menagerialism have been outlined. Last part is devoted to the indications of implemantation of policies inspired by this narrative. Although presenting NPM as an universal trend of evolution of public managment policies is dubious, a coherent conceptualisation based on some discernible trends is still possible.